Initial bystander response to a simulated out-of-hospital cardiac arrest - Fran Wyffels; Geert Brône; Nathalie Charlier; Peter Iserbyt; Stijn De Beugher; Tessy Boedt; Toon Goedemé (International Journal of First Aid Education)
Objective: The main aim was to investigate laypersons’ automatic reactions when confronted with an unexpected, real-life simulated out-of-hospital cardiac arrest (OHCA). Methods: 16 participants with no prior knowledge of cardiopulmonary resuscitation (CPR) were individually confronted with a simulated OHCA, while observing art in a museum, as a deceptive task. Participants wore an eye-tracker and were continuously videotaped to collect their responses. Following the simulated OHCA, participants were interviewed to collect reflections on their reaction and then debriefed by a psychologist. One month later, appearance of posttraumatic stress disorder was requested by mail. Results: The primary outcome was the timing and helping behavior of the layperson. Five of 16 participants noticed the casualty within 40 seconds after collapse and initiated immediate help. Two participants provided no help, although they had noticed the collapsed person. The second outcome was the participants’ reflection on their response to the simulated emergency. The main reasons for delayed helping behavior were a lack of cardiac arrest recognition, misinterpretation of the emergency, bystander effect, and distraction by the deceptive task. Conclusion: Results show the need for public awareness regarding the recognition of cardiac arrest and correct interpretation of an emergency.